Gun Violence and Human Rights - Leila Nadya Sadat; Madaline M. George (Washington University Journal of Law & Policy, 2019)
This article challenges the prevailing narrative regarding gun rights in the United States by viewing them through the lens of human rights. In doing so, it makes five central claims. First, that the U.S. gun violence crisis implicates the rights enshrined in human rights treaties and customary international law. Second, that the U.S. government is responsible for addressing these rights violations. Third, that the U.S. government’s failure to do so is violative of its international human rights obligations. Fourth, that the Second Amendment does not pose a legal bar to the sorts of government actions that would meet this obligation. And, fifth, that both international and domestic remedies are available to those harmed by the U.S. government’s inaction.
Keywords: human rights; gun rights; international law; gun violence